Pursuing a Career in Early and Primary Education: Male Student-Teachers’ Experiences in Jamaica - Lindsay, Theresa (University of Liverpool, 2021)
Researchers have emphasised the need to recruit more men in early childhood and primary education, and governments and policymakers have responded to this need. Despite the recognised value of recruiting more men, the number of men pursuing early childhood and primary education is still insufficient in many places around the world, such as the island nation of Jamaica. The low recruitment in the profession suggests that more focus needs to be placed on understanding the experiences and perceptions of the men who have selected this profession. The purpose of this study was to gain an understanding of the decisions of male student-teachers who pursue careers in early childhood and primary education, based on one Jamaican teacher education college. This is a transcendental phenomenological (TP) study in which eight male student-teachers were interviewed using semi-structured interviews. A well-known systematic approach was chosen to collect, manage, and analyse qualitative data within a TP methodology. However, with the sample size of eight male student-teachers, it is not possible to say whether these findings can be generalised to the study population. Future research on this topic could be expanded across all state-owned teacher education institutions in Jamaica. The findings of this study indicated that male student-teachers are influenced in their career choices by others, the desire to work with children, and the passion for teaching. Participants in this study wanted to make a difference in children’s lives and be positive role models or act as father figures. Most participants had experienced negative reactions from others about their career choice, such as views that men do not have the characteristics to become early childhood or primary education teachers. Many of these negative reactions were based on stereotypical views of gender from others, including female peers with whom they were studying. Because of the perception that such views are predominant in society, a few participants expressed fear of being viewed as sexual predators. These participants suggested such views were perpetuated by the fact that early childhood and primary education continue to be female-dominated environments, with males in the sector being viewed as “others.” While male student-teachers are subjected to discouragements and gender stereotypes, they too demonstrate strong stereotypical views. These views relate predominantly to their perceived value to the profession and aspects of the teaching role that they believe males may be more naturally suited to. The participants provided useful insight into what they felt institutions should do to successfully recruit more male students for early childhood and primary education teaching programmes. The findings of this study have implications for those working in colleges and schools. It is essential that teacher training programmes effectively address gender bias if they wish to avoid perpetuating this in subsequent generations, which will be taught by current student-teachers when they enter the workforce. Unless government challenges the stereotypical views of gender-related roles and behaviours in schools, as well as within teacher training programmes, a gender balance in early childhood and primary education will not be attained.
Keywords: Primary education; Early childhood; Male student-teachers; Gender stereotypes; Female-dominated professions; Jamaica